UPLC-ESI-IT-TOF-MS metabolomic study of the therapeutic effect of Xuefu Zhuyu decoction on rats with traumatic brain injury. (5th December 2019) - Fu, Chunyan; Wu, Qian; Zhang, Zhimin; Xia, Zian; Ji, Hongchao; Lu, Hongmei; Wang, Yang
Abstract: It has been widely reported that Xuefu Zhuyu decoction (XFZYD), a traditional Chinese medicine, is effective in the treatment of traumatic brain injury (TBI). However, the mechanism of the therapeutic process is still not fully understood. Metabolomic technique can be used to explore the mechanisms underlying the treatment of TBI with XFZYD. The purpose of this work was to investigate the metabolic characteristics of blood samples from rats with and without XFZYD treatment and the dynamic changes in metabolite profiles on days 1, 3, 7, 14 and 21 after injury (within the severe phase of TBI) based on untargeted UPLC-ESI-IT-TOF-MS analysis. Pattern recognition, clustering analysis and metabolic pathway analysis were used to analyse the metabolomic data of three groups (a sham-operated group, a TBI model, and an XFZYD-treated TBI model). The results showed that XFZYD reversed the abnormalities in the levels of small-molecule metabolites (such as L-acetylcarnitine, L-tryptophan, indoleacrylic acid, γ-aminobutyric acid, hypotaurine, LysoPC(18:1)(11Z), creatine, L-phenylalanine and L-leucine) in TBI rats through six metabolic pathways (including phenylalanine, tyrosine and tryptophan biosynthesis; phenylalanine metabolism; valine, leucine and isoleucine biosynthesis; taurine and hypotaurine metabolism; tryptophan metabolism; and alanine, aspartate and glutamate metabolism) involved in the therapy process. XFZYD regulated the metabolic disorders of endogenous markers by the possible mechanisms of neuroprotection, energy metabolism, inflammatory response and oxidative stress. This study revealed the holistic and dynamic metabolic changes caused by XFZYD in rats with TBI and provided important research methods and approaches for exploring the multiple metabolites and metabolic pathways involved in the therapeutic effect of XFZYD on TBI. Graphical abstract: Image 1